2015
DOI: 10.1007/s10815-015-0566-3
|View full text |Cite
|
Sign up to set email alerts
|

Association between IL-6 −174 G/C, IL-6 −634 G/C, and IFN-γ +874 A/T polymorphisms and susceptibility to recurrent pregnancy loss: a meta-analysis

Abstract: Objective The aim of this study was to determine whether interleukin-6 (IL-6) −174 G/C, IL-6 −634 G/C, and interferon-γ (IFN-γ) +874 A/T polymorphisms are associated with susceptibility to recurrent pregnancy loss (RPL). Methods We conducted a literature search using PubMed and EMBASE databases and performed a meta-analysis using fixed-or random-effects models. Results A total of 15 articles met the study inclusion criteria. When all study subjects were considered together, metaanalysis showed no association b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…In several studies, the presence of this pro-inflammatory cytokine in serum and peritoneal fluid has been associated with endometriosis [15,17]. The G634C variation (rs1800796), which comprises the exchange of a guanine for a cytosine in the promoter region of the IL-6 gene, may interfere with the expression of IL-6, and therefore, it has been studied as a possible pathogenic mechanism of endometriosis [18].…”
Section: Introductionmentioning
confidence: 99%
“…In several studies, the presence of this pro-inflammatory cytokine in serum and peritoneal fluid has been associated with endometriosis [15,17]. The G634C variation (rs1800796), which comprises the exchange of a guanine for a cytosine in the promoter region of the IL-6 gene, may interfere with the expression of IL-6, and therefore, it has been studied as a possible pathogenic mechanism of endometriosis [18].…”
Section: Introductionmentioning
confidence: 99%
“…Another strength of our study was the careful selection of the gene panel based on the hypothesized biological pathways. We had previous evidence for the association with RPL for some of the variants (within F2 , F5 , ACE , IL10 ) used [ 18 , 28 , 40 ], whereas others (within F7 , GP1A , ESR1 , ADRB2 , ENOS , MTHFR , IL6 , IL8 ) were chosen for their hypothesized biological mechanisms [ 19 , 20 , 25 , 26 , 38 , 42 , 43 , 48 , 51 ]. For the variants where we found an opposite direction of effect with the published results, the ancestry of the studied population differed from ours.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, imbalances in the homeostasis between the fetal and maternal immune system may lead to pregnancy failure [ 39 ]. Variation at the inflammatory gene IL10 has been associated with early PL [ 40 ] and RPL [ 41 ], whereas the evidence for IL6 and RPL is unclear [ 42 ]. MicroRNA studies for endometriosis have shown the potential role of IL-8 levels in the pathogenesis of endometriosis via stimulating endometrial stromal cell invasiveness [ 43 ].…”
Section: Introductionmentioning
confidence: 99%
“…Among the most commonly studied interleukin polymorphisms with regard to their relationship with recurrent pregnancy loss risk are the IL1B rs16944, IL1B rs1143634, IL6 rs1800795, IL6 rs1800796, IL10 rs1800896 and IL18 rs187238 polymorphisms (meta-analyzed in Agrawal et al, 2012;Chen et al, 2015;Lee et al, 2015;Woods et al, 2015;Su et al, 2016). Except for IL1B rs1143634, all other polymorphisms occur in the promoter regions of their genes and are thought to affect the rate of gene transcription.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, IL1B rs1143634 is predicted to disrupt the splicing process (Woods et al, 2015), which can then influence the normal function of IL-1B and, as a result, the risk of recurrent pregnancy loss. The association of these polymorphisms has been investigated in several populations, but few studies have been conducted in the Chinese population (Agrawal et al, 2012;Chen et al, 2015;Lee et al, 2015;Woods et al, 2015;Su et al, 2016).…”
Section: Introductionmentioning
confidence: 99%